Effects of Domiciliary Professional Oral Care for Care-Dependent Elderly in Nursing Homes – Oral Hygiene, Gingival Bleeding, Root Caries and Nursing Staff’s Oral Health Knowledge and Attitudes - Girestam Croonquist, Caroline (Clin Interv Aging, 2020)
PURPOSE: The primary aim was to describe the effects for nursing home residents of monthly professional cleaning and individual oral hygiene instruction provided by registered dental hygienists (RDHs), in comparison with daily oral care as usual. The secondary aim was to study the knowledge and attitudes among nursing staff regarding oral health care and needs. PATIENTS AND METHODS: In this randomised controlled trial (RCT), 146 residents were recruited from nine nursing homes in Regions of Stockholm and Sörmland and were randomly assigned (on nursing home level) to either intervention group (I; n=72) or control group (C; n=74). Group I received monthly professional cleaning, individual oral hygiene instructions and information given by an RDH. Group C proceeded with daily oral care as usual (self-performed or nursing staff-assisted). Oral health-related data was registered with the mucosal-plaque score index (MPS), the modified sulcus bleeding index (MSB), and root caries. The nursing staff’s attitudes and knowledge were analysed at baseline and at six-month follow-up. Statistical analysis was performed by Fisher’s exact test and two-way variance analysis (ANOVA). RESULTS: Improvements were seen in both Group I and Group C concerning MPS, MSB and active root caries. The nursing staff working with participants in Group I showed significant improvements regarding the Nursing Dental Coping Beliefs Scale (DCBS) in two of four dimensions, oral health care beliefs (p=0.0331) and external locus of control (p=0.0017) compared with those working with Group C. The knowledge-based questionnaire showed improvement (p=0.05) in Group I compared with Group C. CONCLUSION: Monthly professional oral care, combined with individual oral health care instructions, seems to improve oral hygiene and may reduce root caries among nursing home residents. This may also contribute to a more positive attitude regarding oral hygiene measures among nursing home staff, as compared with daily oral care as usual.